GEO-ECONOMIC AND GEO-POLITIC POSITION RESOURCES OF THE BACH LONG VY ISLAND - Thanh, Tran Duc; An, Le Duc (Vietnam Journal of Marine Science and Technology, 2014)
As a small island located near the approximately centre of The Gulf of Tonkin, the Bach Long Vi island possesses great values on geo-economic and geo-politic position resources. On the geo-economic resources, the island is a priority site for the country’s sea-island economy development; a central location in the economic space of the Gulf f of Tonkin; belonging directly to Haiphong city-the biggest economic centre in the Northern coastal zone; an advantageous area to develop many marine services such as fishery logiistics, petroleum, tourism, seeking for/and rescue, health, environment, banking and telecom etc. On the geo-politic resources, the island possesses very great values on the determination, enlargement, and guard of national marine sovereignty and benefit; national defense and security concerning the country’s Northern Part; and sea-island culture with the deepfelt love of Vietnam country in the far island.